Bank-firm relationships and corporate ESG greenwashing. - Hongyu Liu (PLoS ONE)
This study explores how bank-firm relationships and executives with banking backgrounds influence greenwashing among Chinese A-share listed firms, based on Institutional and Agency Theories. Firms with bank shareholding or banking-experienced executives show a higher propensity for greenwashing, driven by executive compensation structures tied to inflated ESG scores. Financialization amplifies symbolic ESG disclosures, while transparency reduces greenwashing. Heterogeneity analysis reveals that non-state-owned enterprises and firms in less financially developed regions are more affected. These findings highlight the need for robust governance and transparency to promote authentic ESG practices, offering insights into mitigating greenwashing in emerging markets.